Jelatok Retreat Farm: case study: company analysis / Nur Azmina Syakirah Mohd Nizam … [et al.] - Mohd Nizam, Nur Azmina Syakirah; Nor Azmy, Nur Hazmida Husna; Zunaini, Nuryasmin Zulaikha; Kassim Maniam, Nor Fateha (2021)
Jelatok Retreat Farm is a café and homestay where its café is known as Terrace Café, while its homestay as Rebarn. Jelatok Retreat Farm was established on 25th February 2021 and located at Kampung Jelatok, 71750 Lenggeng, Negeri Sembilan. This place is a strategic places where it is surrounded by hills and flora & fauna. Also, it is not far from the city such as Seremban, Nilai, Semenyih and Kuala Lumpur. Jelatok Retreat farm café, special menu is coffee where they have many varieties of coffee such as mocha, americano, and latte. The cafe also provide a great menu when it comes to food, they combine the traditional food and modern food. The customer can enjoy their food with a beautiful and peaceful nature scenery. Next, Jelatok Retreat Farm homestay or known as Rebarn, the customer can sleep at the homestay with many activities that have been provided when they choose the package of accommodation such as therapeutic trail activity, gardening activity, and flowerpot painting activity. However, the foods and beverages price in the café are standard prices that everyone can enjoy and homestay prices are affordable as there are many activities available while enjoy the beauty of nature. Moreover, the company analysis are measured and analyse by using the Business Model Canvas (BMC) and the elements are customer segments, value proposition, channels, customer relationship, revenue streams, key resources, key activities, key partner, and cost structure. To make it easier to analyse and understand a BMC template has been prepared.